Effect of farming system on donkey milk composition. (11th January 2018) - Valle, Emanuela; Pozzo, Luisa; Giribaldi, Marzia; Bergero, Domenico; Gennero, Maria Silvia; Dezzutto, Daniela; McLean, Amy; Borreani, Giorgio; Coppa, Mauro; Cavallarin, Laura
Abstract: BACKGROUND: Donkey milk is considered as a functional food for sensitive consumers, such as children who are allergic to cow milk. No information is available regarding the effect of farming systems on the quality of donkey milk. The present study aimed to evaluate the effect of the farming system and lactation stage on donkey milk with respect to gross composition, as well as fat‐soluble vitamins and fatty acids (FA). RESULTS: Individual milk samples were collected from lactating jennies ( n = 53) on the six of the largest farms located in North West Italy. The performance of lactating jennies, herd characteristics and feeding strategies were recorded at each milk sampling. The gross composition of the milk, along with the fat‐soluble vitamin content, differed in accordance with the farming system. The lactation stage had limited effects on milk quality. A higher milk fat content corresponded to a higher amount of fresh herbage proportion in the diet, with the highest polyunsaturated fatty acid (PUFA), C18:1c9, C18:3 n ‐3, n ‐3 FA, retinol and α ‐tocopherol content and the lowest concentrations of the FA that are less favorable for human health in the milk of animals fed on only forage diets. CONCLUSION: Extensive farming of dairy donkeys increased the fat content and fat‐soluble vitamin concentration of milk and also altered the FA composition to a more favorable profile for human nutrition. © 2017 Society of Chemical Industry